-9t+-7(-6+-10)=

Simple and best practice solution for -9t+-7(-6+-10)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9t+-7(-6+-10)= equation:


Simplifying
-9t + -7(-6 + -10) = 0

Combine like terms: -6 + -10 = -16
-9t + -7(-16) = 0

Multiply -7 * -16
-9t + 112 = 0

Reorder the terms:
112 + -9t = 0

Solving
112 + -9t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-112' to each side of the equation.
112 + -112 + -9t = 0 + -112

Combine like terms: 112 + -112 = 0
0 + -9t = 0 + -112
-9t = 0 + -112

Combine like terms: 0 + -112 = -112
-9t = -112

Divide each side by '-9'.
t = 12.44444444

Simplifying
t = 12.44444444

See similar equations:

| 2(x+9)=x+29 | | y-47=-41 | | x-40=30 | | 22=9n-(-4) | | 6(n-4)=-54 | | 4(m-2)=1 | | 13=6+6 | | log[5]3+log[5]t+log[5](t+4)=log[5]63 | | -2(10x-1)=-48-10x | | 2(x+2)=3x-8 | | 16-7x=-61 | | 10m+9n+4m= | | -4+6(-6+10h)-4h= | | 1.8d+3=2(.9d-1.5) | | A(x)=2x+8x+14 | | 3m+7=7m+6 | | -12+5k=15-45 | | (9x-6)+(3x+8)= | | 7(2+9g)= | | 7.50x+4.75x=891.25 | | 6(3+5y)+(y-8)=13 | | f(x)=-5x+5 | | -10(-2s+1)+6= | | -3x-10=-9x-2 | | log[b](y-3)-log[b](y-4)=log[b](y+3)-log[b]y | | -8a+7(1+5a)=-17+3a | | -5+20x+5x+10=180 | | 5y-1=2y | | -x+3y=28 | | 2x=5x-1 | | 2(3+4(g+1))=-2 | | 10(1+6x)= |

Equations solver categories